The database POPULATION - Demographic database, Umeå university (Umeå University, 2014)
The database POPULATION contains information about the population development in Sweden’s parishes, cities and municipalities according to the present classification every ten years during the period 1810-1990.

The data has been collected by Christian Svärd, and the Demographic Data Base has digitized the information. The information has mainly been taken from Statistics Sweden’s historical publications. Additional data have been collected from the population forms of the database TABVERK.

The database POPULATION is freely available from the home page of the Demographic Data Base.

Purpose:

The Demographic Database (DDB) is a special unit at Umeå University with activities focused on two main areas: data production and research. DDB creates and makes available population databases, mainly based on historical information in parish registers during the 18th, 19th, and 20th centuries.

I folkmängdsdatabasen finns information om den totala folkmängden i Sveriges församlingar, städer och kommuner enligt nutida indelning vart tionde år under perioden 1810-1990.

Uppgifterna i databasen är ursprungligen insamlade av Christian Svärd. Han har i sin tur överlåtit materialet till Demografiska databasen som registrerat in dem. Folkmängdsuppgifterna kommer huvudsakligen från SCB:s historiska publikationer, medan kompletterande uppgifter har hämtats från Tabellverkets folkmängdsformulär.

Du kan själv söka data ur databasen med hjälp av verktyget Folkmängd 1810-1990 som finns på Demografiska Databasens hemsida.

Syfte:

Demografiska databasen (DDB) är en särskild enhet vid Umeå universitet med inriktning på dataproduktion och forskning. DDB skapar och tillgängliggör befolkningsdatabaser, främst baserade på historisk information från kyrkböcker från 1700-, 1800- och 1900-talen.
Folkmängdsdatabasen - Demografiska databasen
Keywords: demography; demografi; demographic statistics; demografisk statistik; SwedPop; SwedPop; DEMOGRAPHY (POPULATION, VITAL STATISTICS, AND CENSUSES); DEMOGRAFI (POPULATION, VITALSTATISTIK OCH FOLKRÄKNINGAR); Censuses; Folkräkningar; History; Historia